REASON IN THE SHADOW OF STRONG EMOTIONS OR A NEW FACE OF NEW MEDIA: Zizi Papacharissi, Affective Publics: Sentiment, Technology, and Politics. New York, NY: Oxford University Press, 2015. - Loš, Tatjana (Politeia, 2021)
Book review:Zizi Papacharissi, Affective Publics: Sentiment, Technology, and Politics. New York,  NY: Oxford University Press, 2015.
Keywords: book review; affect; media; twitter